Соцреалістична новелістика Бориса Тенети - Стороженко, Ліна; Storozhenko, Lina (Східноєвропейський національний університет імені Лесі Українки, 2015)
Стаття присвячена дослідженню соцреалістичних тенденцій у новелістичній спадщині Бориса Тенети. Акцентується увага на відтворенні автором соціального та політичного становища у країні відповідно до декларованого партією пролетарського мистецького напряму.Article is devoted research socialist realist trends in novellas representative of “Executed Renaissance” of Boris the Tenetа. The paper focuses on the image of a writer of social and political life of the country in the 20–30 years of the twentieth century, according to party directives and dogmas of developing “proletarian” literature. Special attention are works in which the author, on the topic of the day, elevates the revolution and the events of the сivil war. The article also discusses the features of “production” of prose and originality of the class of motives (worker – peasant) in the works of prose. In attention drawn works of short prose, included in the book “In the battle” (1931) and “Everyday” (1934).
Social Realism in Short Stories Boris Tenetа
Keywords: соцреалізм; «пролетарська» література; революційний романтизм; «виробнича» проза; socialist realism; “proletarian” literature; revolutionary romanticism; “production” prose